What you really need to lead : the power of thinking and acting like an owner - Kaplan, Robert Steven, (Harvard Business Review Press, 2015)
"What makes a leader? Can you really learn to lead? You might think that leaders need to be born with the right skills or personality attributes. Perhaps you believe you don't have the right experience or that you need to hold an important job to be a leader. Maybe you believe you need permission to lead. As Harvard Business School professor and business executive Robert Steven Kaplan explains in this powerful new book, leadership is accessible to all of us-today-and it starts with an ownership mind-set. You don't need an invitation to lead. Leadership is a dynamic way of thinking and acting that anyone can take on. For Kaplan, acting as a leader is a function of three key questions: 1. Do you work to figure out what you believe as if you were an owner? 2. Do you take action based on those beliefs? 3. Do you focus on adding value to others and take responsibility for the impact of your actions on others-both positive and negative? The book is full of stories taken from the author's own leadership experience as well as from his work helping various types of leaders and organizations. What's revealed is that leadership is not a role reserved for an elite few blessed with the right skills and key positions-it's about a focus on taking ownership and adding value to others. What's more, leadership is a lifelong journey of learning for which you must take responsibility. It's about learning to ask the right questions and learning to understand yourself. As in his earlier books, Kaplan asks probing questions, provides exercises, and suggests follow-up steps that will help you develop your skills, create new habits, and move you toward reaching your unique potential. What You Really Need to Lead is your key to unlocking the power of thinking and acting like an owner"--